INCREASING STUDENTS’ INTEREST IN THE ART OF MUSIC - Makhmudov , Jakhongir Saminjon ugli (Educational Research in Universal Sciences, 2023)
This article deals with increasing the interest of students of general secondary schools in the art of music and wide promotion of the art of music.